2024
DOI: 10.1590/1519-6984.264642
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Ca/Mg quotient reduces the inhibitory effects of PEG induced osmotic stress on Avena sativa L.

Abstract: Drought is one of the most damaging abiotic stress that hinder plant growth and development. The present study aimed to determine the effects of various Ca/Mg quotients under polyethylene glycol (PEG)–induced osmotic stress on growth, uptake and translocation of Ca and Mg in Avena sativa (L). Plants were grown in nutrient solution supplemented with three different Ca/Mg molar quotients (0.18, 2, and 4). After 30 days plants were exposed to two different PEG (Polyethylene glycol) concentrations (0.6 MPa & 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Salt tolerant plants acquire various physiological and metabolic adaptations to avoid specific ion toxicity, osmotic shock 1 3 , nutrient imbalance 4 and oxidative damage 5 7 . Increase in root and/ or shoot biomass also helps in regulating Na + entry to the xylem or to decrease its transport to the shoot 8 , 9 while excluding and avoiding toxic ions during the process 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Salt tolerant plants acquire various physiological and metabolic adaptations to avoid specific ion toxicity, osmotic shock 1 3 , nutrient imbalance 4 and oxidative damage 5 7 . Increase in root and/ or shoot biomass also helps in regulating Na + entry to the xylem or to decrease its transport to the shoot 8 , 9 while excluding and avoiding toxic ions during the process 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Boron plays a key role in cell wall formation, carbohydrate, Indoleacetic acid (IAA) and Ribonucleic acid (RNA) metabolism, membrane integrity, calcium uptake, translocation of sugars, flowering, pollination and ultimately growth [83][84][85]. The increase in primary branches, pods per plant and pod length is attributed to the role of B in cell elongation and maturation, protein synthesis, development of meristematic tissues and eventually plant growth and yield [86][87][88][89][90]. Jing et al [91] reported that the application of B improves plant dry matter and pods per plant in groundnut.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of metal accumulation, a large number of active free oxygen radicals are formed, which may be the main cause of cell membrane lipid peroxidation, and may also harm the functioning and structure of the cell membrane ( Kamran et al., 2019 ; Rehman et al., 2019 ; Afridi et al, 2022a ; Afridi et al, 2022b ). Excessive ROS production causes oxidative stress, as reported for many crops under heavy metals treatment, and is likely to be commenced by molecular oxygen excitation (O 2 ) to generate singlet oxygen or by electron transfer to O 2 and genesis of free radicals (i.e., O 2− and OH − ) ( Mfarrej et al., 2021 ; Bibi et al, 2024 ). Plant response to oxidative stress also depends on plant species and cultivars, and this ROS production in plants is removed by a variety of antioxidant enzymes, such as SOD, POD, CAT, and APX ( Murtaza et al., 2021 ; Akhtar et al., 2022 ; Ali et al., 2022a ).…”
Section: Discussionmentioning
confidence: 99%